Colour Metallography of Cast Iron - Chapter 3: Spheroidal Graphite Cast Iron (Ⅱ) - Zhou Jiyang (China Foundry, 2010)
Cast iron, as a traditional metal material, has advantages of low total cost, good castability and machinability, good wear resistance and low notch sensitivity, and is still facing tough challenge in quality, property and variety of types etc. Experts and engineers studying and producing iron castings all around world extremely concern this serious challenge. Over more than 30 years, a great of research work has been carried out on how to further improve its property, expand its application and combine cast iron technology with some hi-techs (for example, computer technology). Nevertheless, cast iron is a multi-element and multi-phase alloy and has complex and variety of structures and still has great development potential in structure and property. For further studying and developing cast iron, theoretical research work is important promise, and the study on solidification process and control mechanism of graphite morphology is fundamental for improving property of cast iron and developing new type of cast iron. Metallography of cast iron normally includes two sections: liquid phase transformation and solid phase transformation. The book, Colour Metallography of Cast Iron, uses colour metallography technique to study solidification structures of cast irons: graphite, carbides, austenite and eutectics; and focuses on solidification processes. With progress of modern solidification theory, the control of material solidification process becomes important measure for improving traditional materials and developing new materials. Solidification structure not only influences mechanical and physical properties of cast iron, but also affects its internal quality. The book uses a large amount of colour photos to describe the formation of solidification structures and their relations. Crystallization phenomena, which cannot be displayed with traditional metallography, are presented and more phase transformation information is obtained from these colour metallographic photos.Except for focusing on the effect of high carbon phases in cast iron, in this book, special attention is also paid to the effect of austenite on solidification, graphite morphology, and quality of cast iron; at the same time, the study on the solidification behaviours in the region around eutectic cells and its effects on mechanical properties of cast iron, are also emphasized.